An overview of the indigenous economy in Canada - Alex Chernoff; Calista Cheung (Bank of Canada, 2023)
Attempts to measure aspects of the Indigenous economy in Canada are limited by data availability and quality. Drawing on the most recent data sources and research, we provide an overview of the Indigenous economy in Canada. This includes a discussion of the various characteristics of the Indigenous economy, including the labour market and the business sector, institutional settings, and the state of infrastructure. While several measures suggest economic outcomes have improved for Indigenous Peoples in recent decades, institutional settings and gaps in infrastructure and financing continue to hinder their economic progress. The creation of new institutions is helping Indigenous communities to overcome historic barriers to growth, but continued progress is needed to improve data on the Indigenous economy. This would enable policymakers and Indigenous leaders to measure progress and make informed decisions.
Keywords: E01; E02; N41; N42; O43; P48; 330; Central bank research; Development economics; Financial services; Labour markets; Monetary Policy Transmission; Regional economic developments